"Buy the rumor, sell the news": Liquidity provision by bond funds following corporate news events - Alan Guoming Huang; Russ Wermers; Jinming Xue (University of Cologne, Centre for Financial Research (CFR), 2023)
Using a comprehensive database of corporate news, we find that bond funds trade against the direction of news sentiment. The trading against news phenomenon is concentrated in funds selling on positive news and in the post-financial crisis period when dealer liquidity provision is constrained. Funds in so doing exhibit higher alphas, and a potential source of such alphas is bond price reversals post news events. Our findings highlight that bond mutual funds represent a significant liquidity provider in the corporate bond market and play a complementary role to dealers in corporate news events.
Keywords: G12; G14; G23; G39; 330; Fixed income mutual funds; Corporate bonds; Institutional trading; Public news; Textual analysis